Index pregnancy versus post-index pregnancy in patients with recurrent pregnancy loss. (January 2015) - Greenberg, Tzlil; Tzivian, Liliana; Harlev, Avi; Serjienko, Ruslan; Mazor, Moshe; Bashiri, Asher
Abstract Objective: To compare pregnancy outcomes of two consecutive pregnancies in a cohort of women with recurrent pregnancy loss (RPL), in order to determine the long-term prognosis of women with RPL managed in a dedicated RPL clinic. Methods: A retrospective cohort study including 262 patients with two or more consecutive pregnancy losses followed by two subsequent pregnancies – index pregnancy (IP) and post-index pregnancy (PIP). All patients were evaluated and treated in the RPL clinic in the Soroka University Medical Center. Results: Comparing IP with PIP, no significant difference in perinatal outcome was observed. The perinatal outcome remained encouraging with approximately 73% birth rate (73.7% versus 72.5%; p = 0.83). Only 11% of the women with RPL continued to experience pregnancy losses for two subsequent pregnancies. In a multivariate logistic regression analysis, number of miscarriages pre-Index was the only factor independently associated with birth in the PIP. Conclusion: There is no significant difference between IP and PIP regarding perinatal outcome. Appropriate management in the RPL clinic conferred a significant beneficial effect on long-term pregnancy outcome of a cohort of women with RPL.